Perlindungan Hukum Data Pribadi Konsumen Terhadap Pelaku Usaha Jasa Keuangan - Gian Chelvanno Hiariej; Teng Berlianty; Marselo Valentino Geovani Pariela (Faculty of Law, Universitas Pattimura, 2023)
Introduction: Financial services businesses use personal data in the form of consumer telephone numbers as information and communication to enable the distribution of data and information on financial products, in this case such as credit offers and/or service offers, quickly and directly with consumers or potential consumers.Purposes of the Research: (1.) To know and understand the legal protection of consumers regarding the personal data used. (2.) How is the application of the principle of rights in Consumer Personal Data Law to Financial Financing Service Business Actor.Methods of the Research: The author uses normative juridical law research which obtains data from literature studies in the form of laws, documents, books, magazines and other literature related to writing. Results of the Research: The application of the principle of the right to confidentiality, the right to security and the right to comfort in relation to the consumer's personal data, there are still errors or violations in implementing these principles by business actors or employees of the service business actors. The application in making offers by business actors is wrong, causing consumer discomfort. Which is the real purpose of the consumer protection law and the rules regarding consumer protection in the financial services sector issued by the OJK aimed at protecting consumer rights, one of which is the right to comfort. In SEOJK 12/2014, it is clear that financial services business actors are prohibited from contacting consumers to promote or offer a product through personal communication without any request and approval from consumers.